PENGARUH TINGKAT MINAT PEGAWAI PENGADILAN AGAMA BOJONEGORO TERHADAP KEPUTUSAN BERTRANSAKSI DI BANK SYARIAH MANDIRI BOJONEGORO - fauziah, yunistira (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
ABSTRACTÂ The purpose of this study is 1) to determine the level of interest of Bojonegoro Religious Court Employees to transact with Bojonegoro independent Islamic banks 2) to find out what factors influence the level of interest of Bojonegoro Religious Court employees regarding transaction decisions at Bank Syariah Mandiri in Bojonegoro. This research was conducted with a population of 47 respondents. Data were collected using a questionnaire in the form of a list of statements. The data analysis technique used is multiple linear regression analysis using the SPSS program version 23.0.Based on the results of multiple linear regression analysis obtained F value of 27,647 with a significant level of 0,000 (less than 0.05) which means that simultaneously the perception factor of ease of transaction, the perception of benefits and the perception of trust factors have a significant influence on the level of interest Bojonegoro Religious Court employees to make a decision to transact with Bank Syariah Mandiri Bojonegoro. The coefficient of determination = 0.659 means that 65.9% of the interest level of employees of the Bojonegoro Religious Court to make a transaction decision at the Syariah Mandiri bank Bojonegoro is influenced by the three factors mentioned, namely 1) Perception factor Ease of transactions 2) Perceptions of benefits 3) Perceptions of trust factors, whereas the remaining 34.8% is influenced by other factors beyond those three factors, namely perceptions of ease, perceptions of benefits and perceptions of trust. The t-value of the variable perceptions of ease (X1) is 2.621 with a significance level of 0.012 (smaller than 0.05). The t value of the calculated benefit perception variable (X2) was 2.362 with a significance level of 0.023 (smaller than 0.05). T value of the calculated variable trust perception (X3) of 2.140 with a significance level of 0.038 (smaller than 0.05)Â Keywords: minat transaksi, bank syariah, bank syariah mandiri bojonegoro